Next generation approaches for cartilage repair and joint preservation - Akira Tsujii; Tomoki Ohori; Hiroto Hanai; Norimasa Nakamura (Elsevier, 2024)
Introduction: Articular cartilage plays an important role in the normal biological functions of joints, such as shock absorption and lubrication. Unfortunately, although cartilage is supplied with nutrients, it has a low self-healing capacity owing to the lack of direct blood supply; thus, various treatments have been used to improve the healing of cartilage tissue. Recent treatment strategies in the field of orthobiologics and biomaterials are expected to improve the healing rate of cartilage tissue. Objective: To provide the latest research and clinical results related to cartilage therapy and to clarify their efficacy and expected future role. Methods: A literature search was conducted in October 2023 using the keywords "cartilage therapy, next generation" and a narrative review was conducted separately for nonoperative and operative treatments. Results: Orthobiologics already used in clinical practice include platelet-rich plasma- and mesenchymal stem cell-based therapies. Recent studies using exosomes derived from cell cultures have reported promising nonoperative therapies. Biomaterial-based operative therapy, which eliminates donor-site morbidity, can also be useful. In addition, a therapeutic strategy using induced pluripotent stem cells is also being promoted, and future developments are expected. Conclusions: Various types of orthobiologic-based or biomaterials-based therapeutic strategies have been reported, including cell-free and stem cell-based methods; however, new methods using exosomes or induced pluripotent stem cells have not yet been applied clinically and are expected to be developed in the future. Well-designed clinical trials would reveal its true usefulness and we hope that it will be established as a treatment that can actually be offered to patients.